Multiple solutions for quasilinear elliptic Neumann problems in Orlicz-Sobolev spaces. (13th November 2005) - Halidias, Nikolaos; Le, Vy K.
Abstract : We investigate the existence of multiple solutions to quasilinear elliptic problems containing Laplace like operators (ϕ -Laplacians). We are interested in Neumann boundary value problems and our main tool is Brézis-Nirenberg's local linking theorem.